(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
An estimate of the labile fractions of different trace metals (Mn and Pb) in soil from two dumpsites with complexing agents (EDTA and Citrate) was carried out. The dump sites used for this study receives both commercial and domestic wastes. Physiochemical parameters and the total metal concentrations of the soil was determined, extraction with EDTA and Citrate were used to study the potential metal extraction capacity at different time intervals and the extraction rates of metal released as a function of time (between 0 to 24 hr). The relatively low levels of silt, clay, organic matter and CEC indicates high permeability, hence leachability of heavy metals in the soil and suggest that it might be amenable to remediation by soil washing. The removal efficiency showed that complete solubilization of metals did not occur, as not all the complexing agents added to the soil, was bound to the target metal. This might be due to the presence of other ions such as Ca and Fe which form relatively high stable complexes. EDTA yielded much more than citrate for both metals under consideration. Lead was extracted more than Manganese, which suggest Lead has been more labile in solution than Manganese and EDTA as a stronger complexing agent than citrate. The level of extraction was constant for the period of 60 min to 720 min after which it increased considerably